IMPLEMENTATION OF LEARNING PROCESS IN THE FREEDOM CURRICULUM AT SENIOR HIGH SCHOOL (SMA) 3 SUNGAI KAKAP - Prancisca, Stella; Nurani, Lusia Marliana; Chappell, Cary (Universitas Tanjungpura, 2023)
This study aims to reveal the implementation of the Kurikulum Merdeka [Freedom Curriculum] at the State Senior High School [SMAN] 3 Sungai Kakap which is implemented without completely changing the components of the 2013 Curriculum. This research used the qualitative method with the type of case study on the 10th grade students. The data were collected in the following stages: pre-research, research and post-research. The results of the research show that SMAN 3 Sungai Kakap only implements the Freedom Curriculum in 10th grade; not in 11th grade and 12th grade. This is because it is still a try-out period. The implementation of the Freedom Curriculum is considered by the school to be simpler than the 2013 curriculum. The project-based P5 program at SMAN 3 Sungai Kakap is carried out by students on Fridays with exhibitions of practicum learning outcomes. Even though the Freedom Curriculum has just been implemented at SMAN 3 Sungai Kakap, teachers have received more and better information on student achievement. However, it always requires good experience and knowledge from teachers and educators at the school. The implementation of the Freedom Curriculum at SMAN 3 Sungai Kakap, in addition to the 2013 curriculum, is in the form of a practicum program and teachers